Pengaruh Gaya Kepemimpinan Partisipatif dan Iklim Organisasi Sekolah terhadap Kepuasan Kerja Guru (Studi Kasus pada SD di Sungai Mas Kabupaten Aceh Barat) - Affan, Ibnu; Rizkan, Abqa; Luthfi, Luthfi; Win, Konadi (peusangan, 2024)
Research was conducted on state elementary school teachers in Sungai Mas sub-district, West Aceh Regency. With the aim of analyzing the influence of participative leadership style and school organizational climate on teacher job satisfaction. Quantitative analysis uses a multiple regression model, with a sample of 72 teachers. The research results stated that there was a significant influence with the positive contribution of the principal's participative leadership style on teacher job satisfaction, with an average marginal change of 0.671. There is a significant influence of school climate factors on teacher job satisfaction with an average marginal change of 0.354. And simultaneously the principal's participative leadership style and the school's organizational climate make a positive contribution of 46.1% to teacher job satisfaction.